2019
DOI: 10.1542/peds.2018-3963
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Autism Screening in a Large Pediatric Network

Abstract: BACKGROUND: Universal screening is recommended to reduce the age of diagnosis for autism spectrum disorder (ASD). However, there are insufficient data on children who screen negative and no study of outcomes from truly universal screening. With this study, we filled these gaps by examining the accuracy of universal screening with systematic follow-up through 4 to 8 years. METHODS: Universal, primary care-based screening was conducted using the Modified Checklist for Autism in Toddlers with Follow-Up (M-CHAT/F)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
209
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(230 citation statements)
references
References 27 publications
12
209
0
9
Order By: Relevance
“…Factors hindering population-wide uptake of early detection and intervention can be traced to a wide range of implementation challenges, such as lack of cost-effective and accurate screening tools, challenging time requirements and lack of cost coverage in primary care settings, limited funding for and integration of family supports, among others (Daniels & Mandell, 2014; Guthrie et al, 2019; Honigfeld, Chandhok, & Spiegelman, 2012). Solutions for each of these obstacles will advance implementation of early detection and intervention, but they will not counter an obstacle of a different kind— a perceptual barrier , a prevailing view of ASD, held by many scientists, providers, and policy makers alike, which undermines any discourse advancing the potential benefits of early treatment.…”
Section: Perceptual Barriers To Early Identification and Treatment Ofmentioning
confidence: 99%
“…Factors hindering population-wide uptake of early detection and intervention can be traced to a wide range of implementation challenges, such as lack of cost-effective and accurate screening tools, challenging time requirements and lack of cost coverage in primary care settings, limited funding for and integration of family supports, among others (Daniels & Mandell, 2014; Guthrie et al, 2019; Honigfeld, Chandhok, & Spiegelman, 2012). Solutions for each of these obstacles will advance implementation of early detection and intervention, but they will not counter an obstacle of a different kind— a perceptual barrier , a prevailing view of ASD, held by many scientists, providers, and policy makers alike, which undermines any discourse advancing the potential benefits of early treatment.…”
Section: Perceptual Barriers To Early Identification and Treatment Ofmentioning
confidence: 99%
“…al., 2014), Sri Lanka (Perera, Wijewardena, & Aluthwelage, 2009) and Japan (Kamio et al, 2014) for instance, reported low sensitivity. Studies using the Modified Checklist for Autism in Toddlers (MCHAT) in low socioeconomic or ethnically diverse settings within the USA, reported high false positive rates (Khowaja, Hazzard, & Robins, 2015;Scarpa et al, 2013) or low specificity and low positive predictive values in children of colour and children from lower-income households (Guthrie et al, 2019). A study using the Autism Diagnostic Interview-Revised (ADI-R) reported lower sensitivity and specificity on specific domains in Spanish speaking populations in the USA (Vanegas, Magaña, Morales, & McNamara, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While parental questioning is widely used as a screen for ASD, a number of studies have indicated that this strategy is not optimal [Monteiro et al, 2019;Zwaigenbaum & Maguire, 2019]. The Modified Checklist for Autism in Toddlers with Follow-Up (M-CHAT/F), for example, is reported to have a sensitivity of only 38.8% and a positive predictive value of 14.6% [Guthrie et al, 2019]. Thus, this widely used screening tool detects less than 40% of children who will go on to attain a diagnosis of ASD, and less than 15% of the children who are positive on the test actually end up with a diagnosis of ASD.…”
Section: Introductionmentioning
confidence: 99%